SISTEM PAKAR PENANGANAN GANGGUAN MESIN LOKOMOTIF CC201 PADA PT. KERETA API INDONESIA (PT. KAI) BERBASIS WEB (Information Technology and Telematics, 2014)
Abstract - Troubleshooting Expert System CC201 locomotive engine at PT. Kereta Api Indonesia (PT. KAI) is a web-based system that can be accessed through the web, which is where this system can be used as one method for handling disturbances CC201 locomotive engines used on PT.KAI today. The input of the expert system in the form of questions disorder symptoms that must be filled by the user, from the data input system symptoms symptoms will process the data with the appropriate type of disorder. Once the process is completed and data analysis has been found then the interference analysis results will be displayed along with the type of disturbance handling solutions. This expert system design is built using PHP with MySQLdatabase. The conclusion that can be drawn that the mechanic or machinist often experience interference from CC201 locomotive she lived, and with the lack of knowledge in analyzing the interference it takes a lot of time to handle it with this system is expected to shorten the time to treatment of the disorder. Keywords Expert systems, CC201 locomotive disorders, PHP, MySQL Abstrak - Sistem Pakar Penanganan Gangguan Mesin Lokomotif CC201 Pada PT. Kereta Api Indonesia (PT. KAI) berbasis web adalah sebuah sistem yang dapat diakses melalui web, yang dimana sistem ini dapat dijadikan sebagai salah satu metode untuk penanganan gangguan mesin lokomotif CC201 yang digunakan pada PT.KAI saat ini. Input dari sistem pakar ini berupa pertanyaan gejala-gejala gangguan yang harus diisi oleh pengguna, dari data gejala yang diinputkan sistem akan memproses data gejala dengan jenis gangguan yang sesuai. Setelah proses analisa selesai dan data gangguan telah ditemukan maka hasil analisa jenis gangguan akan ditampilkan beserta solusi penanganannya. Perancangan sistem pakar ini dibuat menggunakan bahasa pemrograman PHP dengan database MySQL. Kesimpulan yang dapat diambil bahwa mekanik maupun masinis sering mengalami gangguan dari lokomotif CC201 yang dijalaninya, dan dengan kurangnya pengetahuan dalam menganalisa gangguan maka banyak waktu yang dibutuhkan untuk penanganannya maka dengan sistem ini diharapkan bisa memperpendek waktu penanganan gangguan tersebut. Kata kunci Sistem pakar, gangguan lokomotif CC201, PHP, MySQL